Mental wellbeing of frontline health workers post-pandemic: lessons learned and a way forward - Grünheid, Thorsten; Hazem, Ahmad (Frontiers in Public Health, 2023)
Objective: To assess the state of mental wellbeing among medical and dental frontline health workers two years after pandemic onset and to determine what employer-provided intervention strategies these workers perceive as effective and desirable to improve their mental wellbeing. Methods: An anonymous online survey distributed to frontline health workers in a hospitalist program of a tertiary care medical center and a university dental school in Minnesota in September 2022. The survey contained validated tools to measure depression severity, levels of perceived stress, and mental health status as well as questions to determine effective strategies to improve emotional wellbeing among these health workers. Data was evaluated on an aggregate level as well as stratified by level (e.g., physician, staff) and field (e.g., medicine, dentistry). Results: On average, all groups of health workers suffered from moderate to moderately severe depression, had a much higher perceived stress level than average, and had a fair mental health status. There were no significant differences in depression severity, stress level, or mental health status among physicians, dentists, medical staff, and dental staff. The majority of the respondents perceived adjusted work hours, rewards and incentives, and teamwork as the most effective and desirable strategies to improve their mental wellbeing. Conclusions: Two years into COVID-19, the mental wellbeing of frontline health workers is poor. Many are dissatisfied with healthcare and consider leaving the industry. To improve their employees’ mental wellbeing, healthcare employers might want to consider adjusted work hours, rewards, and teamwork as these intervention strategies are perceived as most effective and desirable by the intended recipients.